Organ-Specific Expression of IL-1 Receptor Results in Severe Liver Injury in Type I Interferon Receptor Deficient Mice - Anzaghe, Martina; Resch, Theresa; Schaser, Elea; Kronhart, Stefanie; Diez, Clara; Niles, Marc A.; Korotkova, Eugenia; Schülke, Stefan; Wolfheimer, Sonja; Kreuz, Dorothea; Wingerter, Marion; Bartolomé Rodríguez, María Matilde; et al. (Frontiers in Immunology, 2019)
Upon treatment with polyinosinic:polycytidylic acid [poly(I:C)], an artificial double-stranded RNA, type I interferon receptor-deficient (IFNAR−/−) mice develop severe liver injury seen by enhanced alanine aminotransferase (ALT) activity in the serum that is not observed in their wildtype (WT) counterparts. Recently, we showed that liver injury is mediated by an imbalanced expression of interleukin (IL)-1β and its receptor antagonist (IL1-RA) in the absence of type I IFN. Here we show that despite comparable expression levels of IL-1β in livers and spleens, spleens of poly(I:C)-treated IFNAR−/− mice show no signs of injury. In vitro analyses of hepatocytes and splenocytes revealed that poly(I:C) had no direct toxic effect on hepatocytes. Furthermore, expression levels of cytokines involved in other models for liver damage or protection such as interferon (IFN)-γ, transforming growth factor (TGF)-β, IL-6, IL-10, IL-17, and IL-22 were comparable for both organs in WT and IFNAR−/− mice upon treatment. Moreover, flow cytometric analyses showed that the composition of different immune cells in livers and spleens were not altered upon injection of poly(I:C). Finally, we demonstrated that the receptor binding IL-1β, IL1R1, is specifically expressed in livers but not spleens of WT and IFNAR−/− mice. Accordingly, mice double-deficient for IFNAR and IL1R1 developed no liver injury upon poly(I:C) treatment and showed ALT activities comparable to those of WT mice. Collectively, liver injury is mediated by the organ-specific expression of IL1R1 in the liver.